The Relationship of Knowledge of Diabetes Mellitus Patients with Diabetes Mellitus Diet Adherence at RSUD.Rantau Prapat, Labuhan Batu District, North Sumatra Province in 2022 - Harahap, Ali Asman; Hutagaol, Aureliya; Basuki, Basuki (Jurnal Kesehatan, Rekam Medis dan Farmasi (JUK-Medifa), 2023)
Diabetes Mellitus (DM) is a chronic disease characterized by blood glucose levels exceeding normal and impaired carbohydrate, fat and protein metabolism caused by relative and absolute lack of the hormone insulin. If this is left uncontrolled it can become an acute metabolic complication as well as a long-term vascular complication of both microangiopathy and macroangiopathy (Darmono in Hasdianah, 2012). Method: This study aims to determine the relationship between diabetes self-management and the level of stress undergoing a diet of DM sufferers at the Rantau Prapat Health Center. This study used a cross sectional design. Respondents were selected from five Puskesmas in Puskesmas Rantau Prapat using the purposive sampling method. A total of 37 DM sufferers participated in the study. Data were collected using DM knowledge questionnaire, then data were analyzed using Chi Square test with significance level <0.05. Results: The results showed that and there was a relationship between knowledge of diabetes mellitus patients with DM diet adherence (p = 0.017), which Conclusion: There was a relationship between diabetes self-management and the level of stress undergoing a diet of diabetics in Puskesmas Rantau Prapat. Future research is expected to use respondents with a wider area and use better measuring instruments.